Resource Allocation Influence on Performance of County Government Funded Water Projects in Kisii County, Kenya - Mutuku, Miombe; Kwasira, Josephat; Lango, Benard (Journal of Public Policy and Administration, 2024)
Purpose: The aim of the study was to examine how resource allocation influences performance of M&E practices on county government funded water projects in Kisii County. Methodology: The study will adopt a descriptive survey design. The study target population includes 201 county water staff managing 90 water projects across the county. The census method was used to research the 201 staff involved in water projects. The primary data was collected by use of questionnaires and Key Informant interviews. Quantitative data was analyzed by employing descriptive statistics and inferential analysis, and the results were presented by tables and figures. Whereas, qualitative data was done through narrative analysis and presented in form of verbatim and narrations. Findings: findings indicated that a mere 12.9% of the participants agreed that the county government allocated a specific budget for M&E activities, while 12.4% strongly agreed. However, a significant 38.2% disagreed with this allocation. Similarly, the budget's adequacy came under scrutiny, with only 3.5% deeming it sufficient, while 37.6% disagreed. Infrastructure provision for M&E activities raised uncertainty among 8.8% of respondents, and only 16.5% agreed on its adequacy. Furthermore, while the allocation of adequate human resources for M&E garnered strong agreement (31.8%), it was met with disagreement by 14.7% of participants. Unique Contribution to Theory, Practice and Policy: This study was anchored in the change theory. The county government of Kisii County can capitalize on this finding by prioritizing adequate resource allocation for M&E activities. This capitalizing may involve dedicating specific budgets, ensuring infrastructure provision, and allocating sufficient human resources. Policymakers and project managers should closely evaluate the resource allocation process, addressing concerns raised by participants in the study. Adequate resources lay the foundation for streamlined operations, data collection, and stakeholder engagement. By recognizing the strategic significance of resource allocation, the county government can significantly enhance the efficiency and effectiveness of water project implementation.